(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
HRM practices and employee satisfaction has been a leading area of study in government sector all over the world. The influence of HRM practices on the satisfaction of employees has been in debates by scholars in the past. Accordingly, the aim of this study is to examine the impact of HRM practices on job satisfaction in Federal Authority for Identity and Citizenship (ICA) in UAE. To achieve this aim, quantitative methods was used and survey on selected sample consists of 377 respondents working in ICA. The result of this study revealed that HRM practice has a significant effect on job satisfaction. This result lead to a final conclusion that HRM practices and job satisfaction are fundamental variables to the work of government organizations. Therefore, to achieve success in public workplace, it is essential to focus on the factors that influence HRM practices such as planning, recruitment of new staff, and compensations.